SEMI-CONTINUOUS CULTIVATION OF CHLORELLA VULGARIS USING COMPOST AS A NUTRIENT SOURCE FOR BIOMASS AND BIODIESEL PRODUCTION - TAN , XIN BEI (2018)
Recently, microalgae biomass has been highlighted as the most feasible feedstock for biofuel production. Microalgae are a group of microorganisms which have simple cellular structure and able to manufacture and store triacylglycerols (TAGs) within their cells especially under stress environment. TAGs are usually present in the cell in the form of storage lipids. Of late, microalgae have become an important feedstock for biodiesel production due to their high lipid content within their cells and they can be reproduced rapidly